Research trends on environmental, social, and governance in SMEs: A bibliometric analysis - Harventy, Gina; Hamid, Fatima Abdul; Yassin, Fatimah Mat; Mokhtar, Norsyahida Binti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study used a scoping review and bibliometric analysis to analyze all publications on Environmental, Social, and Governance (ESG) study trends, specifically in the context of Small and Medium Enterprises (SMEs).Design/Methodology/Approach: Ninety-four (94) ESG articles on SMEs indexed in the Scopus database were described through coverage and bibliometric analysis. The articles were analyzed based on the number of publications per year, contributing countries, authors, and cited documents. Furthermore, VOSviewer was used to provide a visual analysis of keyword occurrences.Research findings: The growing body of research on ESG in SMEs reflects an increasing global awareness of its significance. Notably, publications on this topic have surged year after year, with Asia leading the discourse and Europe following closely. Among individual countries, China and Italy stand out as the most prolific contributors. This upward trend underscores the rising importance of ESG in SMEs, positioning it as a critical area of discussion among international scholars.Theoretical contribution/ Originality: This paper analyzes ESG research trends in SMEs, mapping key developments and gaps. Synthesizing past studies highlights critical insights and future research directions, positioning ESG in SMEs as a growing global discourse.Research limitation/Implication: This study is limited to the Scopus database and focuses solely on ESG research in SMEs. It used only one bibliometric analysis tool to evaluate research trends, which may not capture a broader perspective from other databases or analytical approaches.